Response of Growth and Production of Mustard Greens (Brassica juncea L.) by Administering NPK 16:16:16 Using a Wick Hydroponic System - Evi Julianita Harahap; Amitalia Tumanggor; Juldi Saputra; Mawaddah Putri Arisma Siregar; Muhammad Afrillah; Sumeinika Fitria Lizmah; Chairuddin; Yuliatul Muslimah; Hilmina Itawarnemi; Dedi Kurniawan (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
Wick hydroponics is a simple hydroponic method because it uses a wick to connect the nutrients to the roots of the plant. NPK 16:16:16 is a compound fertilizer that contains balanced nutrients N, P and K, each amounting to 16%. The objective of this study was to determine the response of growth and production of mustard greens (Brassica juncea L.) to NPK 16:16:16 in a wick hydroponic system. The research was conducted at the UF (University Farm) of Teuku Umar University, Meureubo District, West Aceh Regency, in December-January 2024. The study employed a non-factorial Completely Randomized Design (CRD) with 10 concentrations of NPK 16:16:16 fertilizer and 3 replications, yielding a total of 30 experimental units. Each experimental unit consisted of three sample plants grown in a single Styrofoam container, giving a total of 90 sample plants. The NPK 16:16:16 fertilizer concentrations evaluated were 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, and 5.0 g L⁻¹. Analysis of variance data using SPSS version 25 software with the DMRT (Duncan Multiple Range Test) as a further test. The results of the research showed that the provision of NPK 16:16:16 fertilizer had a significant effect on the growth of mustard greens, as indicated by differences in plant height, number of leaves, leaf length and leaf width. Providing NPK 16:16:16 fertilizer resulted in a significant difference in mustard green production, as measured by plant wet weight and plant dry weight. Based on the research findings, the application of NPK 16:16:16 fertilizer was shown to enhance vegetative growth and yield of mustard greens grown in the wick hydroponic system, thereby increasing crop productivity. The application of NPK 16:16:16 fertilizer at a concentration of 0.5 g/L is recommended for mustard green cultivation in a wick hydroponic system as an effective fertilization alternative to improve plant growth and increase harvest yield.